Enhancing local revenue with land and construction tax incentives: fair and balanced tax approaches - Kusumastuti, Dora; Musa , Hussein Gibreel (Journal of Law, Environmental and Justice, 2023)
PBB-P2 tax (Land and Building Tax-Rural and Urban) and other valid sources provide local revenue. In article 10 of Regulation of the Minister of Finance of the Republic of Indonesia Number 208/PMK.07/2018 for the Assessment of Rural and Urban Land and Building Taxes, "The Regional Head determines the amount of NJOP (Tax Object Selling Value) of Land and Building every 3 (three) years, except for certain tax objects that can be determined annually in accordance with the development of the region." One technique to optimize PBB revenue is to update NJOP data. One way to enhance municipal revenue legally is with a tax stimulus. Empirical legal research uses induction reasoning to analyze primary and secondary data. The goal is to determine a lawful and compliant local tax optimisation policy. NJOP is significantly higher now. NJOP increases by 1–8 times. Through a mayoral regulation on PBB-P2 stimulus in 2023–2025, the Local Government hopes to reduce social turmoil by gradually increasing the value of the Land and Building Tax assessment.